Peripheral vascular structure and function in hypertrophic cardiomyopathy - Rowley, N. J.; Green, D. J.; George, K.; Thijssen, D. H. J.; Oxborough, D.; Sharma, S.; Somauroo, J. D.; Jones, J.; Sheikh, N.; Whyte, G. (British Journal of Sports Medicine, 2012)
Background: Hypertrophic cardiomyopathy (HCM) is characterised by idiopathic cardiac enlargement and represents the most frequent cause of sudden cardiac death in athletes under the age of 35 years. Differentiation between physiological (ie, exercise-related) and pathological (ie, HCM-related) cardiac remodelling is challenging. In line with cardiac remodelling, vascular structure and function are altered following training, but little is known about peripheral vascular adaptations in HCM. We hypothesised that, while HCM patients and athletes would exhibit similar cardiac characteristics, differences would be apparent in their brachial and carotid arteries. Methods: In age-matched groups of HCM patients (n=18, 39±15 years), highly competitive athletes (n=18, 38±12 years) and recreational controls (n=10, 37±14 years), we used high-resolution ultrasound to assess the diameter and wall thickness of the carotid and brachial arteries, with flow-mediated dilator function (FMD) of the brachial arteries also assessed. Results: A significant difference between athletes and HCM was evident in arterial wall thickness (carotid 519±60 vs 586±102 µm, p<0.05; brachial 345±80 vs 456±76 µm, p<0.05) and the brachial artery peak blood flow response following forearm ischaemia, an index of resistance artery remodelling (998±515 vs 725±248 ml/min, p<0.05). Similar differences were noted between athletes and controls, while controls and HCM did not differ. Brachial FMD% was not different between groups. Conclusions: Athletes and HCM subjects, who can be difficult to differentiate on the basis of cardiac measures, exhibit differences in indices of arterial structure. While this may be a disease-related effect, we cannot discount a generic impact of physical activity on arterial structure, as the athlete's arteries were also different to untrained control subjects. Future studies should assess artery function and structure in athletic HCM subjects.